New generation drug‐eluting stents for ST‐elevation myocardial infarction: A new paradigm for safety. Issue 6 (11th August 2014) - Garg, Ankit; Brodie, Bruce R.; Stuckey, Thomas D.; Garberich, Ross F.; Tobbia, Patrick; Hansen, Charles; Kissling, Grace; Kadakia, Hemal; Lips, Daniel; Henry, Timothy D.
<x xml:space="preserve">Abstract</x> Objectives The objective of this study is to compare the long‐term safety of new generation drug‐eluting stents (DES) with early generation DES and bare metal stents (BMS) for ST‐segment elevation myocardial infarction (STEMI). Background Early generation DES for STEMI have reduced target vessel revascularization, but have more very late ST compared with BMS raising concerns about their safety. New compared with early generation DES have lower rates of ST, but there are limited data in STEMI patients. Methods From 2003 to 2011, 3, 464 STEMI patients were treated with BMS (n = 1, 187), early generation DES (n = 1, 525), or new generation DES (n = 752) and were followed for 1–9 years. Results Patients with new generation DES were younger, had less cardiogenic shock, and less prior infarction versus BMS, and more hypertension versus early generation DES. At 2 years, new generation DES had lower mortality (4.0% vs. 12.4%, P < 0.001), similar reinfarction (4.4% vs. 5.1%, P = 0.35), and less ST (1.4% vs. 3.8%, P = 0.031) versus BMS; and similar mortality (4.0% vs. 5.8%, P = 0.23), similar reinfarction (4.4% vs. 5.2%, P = 0.64), and trends for less ST (1.4% vs. 3.3%, P = 0.17) versus early generation DES. By Cox multivariable analyses, BMS had more ST than new generation DES (HR [95% CI] = 1.93 [1.01–3.66], P = 0.045). Conclusions New generation DES in STEMI patients have less ST compared to BMS and trends for less ST compared to early generation DES. These data suggest a new safety paradigm and should encourage the use of new generation DES in most STEMI patients treated with primary percutaneous coronary intervention (PCI). © 2014 Wiley Periodicals, Inc.